2021
DOI: 10.3390/biomedicines9081001
|View full text |Cite
|
Sign up to set email alerts
|

Genes Common in Primary Immunodeficiencies and Cancer Display Overrepresentation of Codon CTG and Dominant Role of Selection Pressure in Shaping Codon Usage

Abstract: Primary immunodeficiencies (PIDs) are disorders of the immune system that involve faulty cellular, humoral, or both cellular and humoral functions. PIDs are present at the crossroad between infections, immune dysregulation, and cancers. A panel encompassing 42 genes involved in both PIDs and cancer has been investigated for the genes’ compositional properties, codon usage patterns, various forces affecting codon choice, protein properties, and gene expression profiles. In the present study, the codon choice of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
6
13
0
Order By: Relevance
“…The %GC3 content was the most variable compositional parameter and varied between 41.80% and 83.82%. The highest variability in %GC3 and least occurrence of %T in the present study is in concordance with the study of Khandia et al (2021) (36), who reported the same results in the genes common in primary immunodeficiencies and cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The %GC3 content was the most variable compositional parameter and varied between 41.80% and 83.82%. The highest variability in %GC3 and least occurrence of %T in the present study is in concordance with the study of Khandia et al (2021) (36), who reported the same results in the genes common in primary immunodeficiencies and cancer.…”
Section: Discussionsupporting
confidence: 93%
“…However, CUB and protein length were positively correlated with GC3 content higher than GC12 content in all the proteins envisaged without any exception. Our results agree with Khandia et al (2021) (36), who found that in all the proteins of size ranging between 150 and 3000 amino acids, GC12 content was lower than GC3 without any exception.…”
Section: Discussionsupporting
confidence: 93%
“…Even though we did not find a correlation between the CpG and TpG/CpA, TpG dinucleotide-containing codons CTG and GTG were over-represented in 74.46 and 68.08% genes, respectively, while all CpG-containing codons (CGT, GCG, ACG, CCG, and TCG) were under-represented (in 53.19, 72.34, 57.44, 70.21, and 78.72% genes respectively). CTG codon has been over-represented in genes common in primary immunodeficiencies and cancer ( Khandia et al, 2021 ). The same has been depicted in genes associated with brain iron accumulation (Alqahtani et al, 2021) ( Alqahtani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aliphatic index is a suggestive of volume gained by aliphatic side chains. An instability index with an aliphatic index reveals the stability of a protein ( Khandia et al, 2021 ). The isoelectric point is a value where no net electric charge on protein is present, and solubility is minimal ( ScienceDirect Topics, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding CVID, only 20% of cases are caused by monogenic defects; the remaining 80% derives from polygenic variants and/or from epigenetic alterations [30,31]. Interestingly, a study recently published by Khandia et al considering a panel of 42 genes involved both in PID and cancer highlighted how these genes are under a selection pressure [32]. These cases can be successfully identified crossing whole genome sequencing (WGS) or whole exome sequencing (WES) with RNAseq methods to discover gene-gene interactions and expression dysregulations not detectable by genomic studies only [33][34][35].…”
Section: Discussionmentioning
confidence: 99%